2010
DOI: 10.1371/journal.pcbi.1000797
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of GABAergic Inhibition Promotes Strengthening of Temporally Coherent Inputs among Convergent Pathways

Abstract: Spike-timing-dependent plasticity (STDP), a form of Hebbian plasticity, is inherently stabilizing. Whether and how GABAergic inhibition influences STDP is not well understood. Using a model neuron driven by converging inputs modifiable by STDP, we determined that a sufficient level of inhibition was critical to ensure that temporal coherence (correlation among presynaptic spike times) of synaptic inputs, rather than initial strength or number of inputs within a pathway, controlled postsynaptic spike timing. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 79 publications
(115 reference statements)
3
40
2
Order By: Relevance
“…This may reflect increased involvement of this source of inhibition in more mature cortical circuits. The developmental profile of PV cells was consistent with previous studies (Doischer et al 2008;Okaty et al 2009;Kuhlman et al 2010) and demonstrated the postnatal acquisition of fast-spiking characteristics (McCormick et al 1985).…”
Section: Cell Type-specific Maturation Of Spiking Propertiessupporting
confidence: 90%
See 2 more Smart Citations
“…This may reflect increased involvement of this source of inhibition in more mature cortical circuits. The developmental profile of PV cells was consistent with previous studies (Doischer et al 2008;Okaty et al 2009;Kuhlman et al 2010) and demonstrated the postnatal acquisition of fast-spiking characteristics (McCormick et al 1985).…”
Section: Cell Type-specific Maturation Of Spiking Propertiessupporting
confidence: 90%
“…Postnatal development of layer II/III pyramidal cells leads to lower input resistance (Luhmann and Prince 1991;Desai et al 2002;Kuhlman et al 2010) and hyperpolarized V M (Luhmann and Prince 1991;Desai et al 2002; M. S. Lazarus and Z. J. Huang, unpublished observations), which should reduce cell excitability. The substantial increase of excitability of SOM cells may reflect a stronger engagement of this type of inhibition in V1 circuits during the critical period.…”
Section: Maturation Of Dendrite-targeted Inhibition From Somatostatinmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, PV Basket cells inhibit each other reciprocally through perisomatic innervation and are dynamically coupled electrically through gap junctions (Bartos et al, 2007;Hu et al, 2014). As a result, PV Basket cells filter activation of principal neurons, and networks of PV Basket cells have major roles in regulating local ensemble activities, including theta and gamma oscillations (Fuchs et al, 2007;Cardin et al, 2009;Kuhlman et al, 2010;Isaacson and Scanziani, 2011;Lee et al, 2012;Hu et al, 2014). Synaptic regulation of PV Basket cells has been implicated in adult learning, and the maturation state of PV Basket cells has been implicated in critical period-type plasticity (Hensch et al, 1998;Hensch, 2005;Di Cristo et al, 2007;Southwell et al, 2010;Kuhlman et al, 2013;Wolff et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This process is experience dependent, that is it cannot begin before eye opening, after which the critical period for setting ocular dominance and visual acuity is started (Fagiolini and Hensch, 2000;Sugiyama et al, 2009). Pv-interneurons in the visual cortex mature in connections (e.g., forming perisomatic synapses on principal neurons) and intrinsic firing properties (e.g., fast spiking) by the end of the critical period, thus allowing the firm functional cortical connections for binocular visual acuity to be formed (Kuhlman et al, 2010). PNNs interact with receptors such as NgR1 (NoGo receptor) and leukocyte common antigene-related phosphatase (Akbik et al, 2013;Ye and Miao, 2013).…”
Section: F Developmental Neuroplasticity: Critical Periods Reopeninmentioning
confidence: 99%